Kepemilikan Manajerial Dan Komisaris Independen Sebagai Faktor Penentu Cost Of Equity Capital Pada Perusahaan Manufaktur Aneka Industri Di Indonesia - Herman Wijaya; Dian Maulita; Dien Sefty Framita (Jurnal Akuntansi Manajemen (JAKMEN), 2023)
This study aims to analyze the influence of Managerial Ownership, Cost of Equity Capital. This study uses the objects of manufacturing companies in the Various Industries sub-sector on the Indonesia Stock Exchange for the 2017-2020 period. The data used is secondary data in the form of the company's annual financial report. The analytical tool used to test the hypothesis is IBM SPPS V26. The sampling method used in this study used a purposive sampling technique and obtained 38 companies with 152 sample data. The analysis technique used is descriptive statistical analysis, classical assumption test, multiple regression analysis, t (partial) test. The results of the study conclude that: 1) Managerial ownership has a negative and significant effect on the Cost of Equity Capital, 2) Independent commissioners have a negative and significant effect on the Cost of Equity Capital,